Fair Bandwidth Sharing among Virtual Machines in a Multi-criticality Scope - Grösbrink, Stefan; Almeida, Luis; de Sousa, Mario; Petters, Stefan M. (5th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2013))

Accelerating Online Model Checking - Qanadilo, Mona; Samara, Sufyan; Zhao, Yuhong (6'th Latin-American Symposium on Dependable Computing (LADC 2013))

Bildangereicherte Kartenerstellung zur Unterstützung bei Rettungseinsätzen - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Statistisches Planen in einem realen Roboterszenario - Rasche, Christoph; Bieshaar, Maarten; Jungmann, Alexander; Kleinjohann, Lisa; Kleinjohann, Bernd (Entwurf mechatronischer Systeme, Verlagsschriftenreihe des Heinz Nixdorf Instituts, Paderborn, Band 310)

Architecture for Adaptive Resource Assignment to Virtualized Mixed-Criticality Real-Time Systems - Grösbrink, Stefan; Baldin, Daniel; Oberthür, Simon (ACM SIGBED Review, Band 10)

SystemC Verification Components - An enhanced OVM/UVM for SystemC - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (edaWorkshop 13)

Funktionale Verifikation von Low-Power Designs unter Verwendung Virtueller Prototypen - Mischkalla, Fabian; Müller, Wolfgang (Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV))

SC OVM: An Advanced SystemC Library for OVM-based Verification - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (Open SANITAS SystemC Verification Workshop)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Müller, Wolfgang (ForschungsForum Paderborn)

Basics of Virtual Machine Migration on Heterogeneous Architectures for Self-optimizing Mechatronic Systems - Necessary Conditions and Implementation Issues - Grösbrink, Stefan (Production Engineering Research & Development 7(1))

Learning Service Recommendations - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa (International Journal of Business Process Integration and Management 6(4))
The as a service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilised on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our approach of modelling this service composition and recommendation process as Markov decision process and of solving it by means of reinforcement learning. A case study serves as proof of concept.

Systematic Application of UCIS to Improve the Automation on Verification Closure - Kuznik, Christoph; Oliveira, Marcio F.; Defo, Bertrand; Müller, Wolfgang (Proceedings of DVCON)

A 3D Path Planning Approach Extended by Bifurcation Theory for Formation Flights - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (Recent Advances in Robotics and Automation, Studies in Computational Intelligence, Band 480)
After big disasters, search and rescue missions take place. During these missions it is essential to obtain an overview of the overall situation to arrange efficient rescue tasks as soon as possible. Afterwards, this information has to be continuously updated during the complete mission in order to quickly respond to changing conditions. The use of unmanned aerial vehicles (UAVs) is a viable choice to obtain such an overview in a fast and efficient way. Using multiple UAVs, the problem of coordination has to be solved to decrease the time needed to explore an area. We present an approach for the coordination of UAVs by setting up formation patterns using bifurcation theory. We combine this theory with a potential field approach for exploration, based on harmonic functions.

Fault-Tolerant Deployment of Real-Time Software in AUTOSAR ECU Networks - Klobedanz, Kay; Jatzkowski, Jan; Rettberg, Achim; Müller, Wolfgang (International Embedded Systems Symposium (IESS) 2013)

Automatic Reconstruction of Polygonal Room Models from 3D Point Clouds - Mertsching, Bärbel; Divband Soorati, Mohammad; Kotthauser, Tobias (IEEE International Conference on Robotics and Biomimetics (ROBIO))

Time delay implies cost on task switching: A model to investigate the efficiency of task partitioning - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas (Bulletin of Mathematical Biology)

Algorithmic Requirements for Swarm Intelligence in Differently Coupled Collective Systems - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Zahadat, Payam (Chaos, Solitons & Fractals)

Virtual Spatiality in Agent Controllers: Encoding Compartmentalization - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Schwarzer, Christopher; Michiels, Nico K.; Esparcia-Alcazar, Anna Isabel (Applications of Evolutionary Computation - 16th European Conference (EvoApplications 2013))

A Reductionist Approach to Hypothesis-Catching for the Analysis of Self-Organizing Decision-Making Systems - Hamann, Heiko (7th IEEE Int. Conf. on Self-Adaptive and Self-Organizing Systems (SASO 2013))

Speciation Dynamics: Generating Selective Pressure Towards Diversity - Hamann, Heiko; Lio, Pietro; Miglino, Orazio; Nicosia, Giuseppe; Nolfi, Stefano; Pavone, Mario (12th European Conference on Artificial Life (ECAL 2013))

Towards Swarm Calculus: Urn Models of Collective Decisions and Universal Properties of Swarm Performance - Hamann, Heiko (Swarm Intelligence)

Themenmodellierung zur Identifikation und Gruppierung von Spam-Webseiten - Laudemann, Stefan

Nichtapproximierbarkeitsresultate zu Radius- und Durchmesserclustering unter Verwendung von L_p-Metriken - Leder, Lennart

A heuristic energy-aware approach for hard real-time systems on multi-core platforms - He, Da; Müller, Wolfgang (Microprocessors and Microsystems - Embedded Hardware Design 37(6-7))

Embedded Systems: Design, Analysis and Verification. Proceedings of the 4th IFIP TC10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 2013

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz-Josef (The Ninth International Conference on Autonomic and Autonomous Systems)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (J. Cryptology)

Practical Signatures from Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Hong Seo, Jae; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2013, 32nd Annual International Conference on the Theory and Applications of Cryptographic Techniques, Athens, Greece, May 26-30, 2013. Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Bounded Model Checking of Graph Transformation Systems via SMT Solving - Isenberg, Tobias; Steenken, Dominik; Wehrheim, Heike (Formal Techniques for Distributed Systems - Joint IFIP WG 6.1 International Conference, {FMOODS/FORTE} 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings)

SPIN as a Linearizability Checker under Weak Memory Models - Travkin, Oleg; Mütze, Annika; Wehrheim, Heike (Hardware and Software: Verification and Testing - 9th International Haifa Verification Conference, HVC 2013, Haifa, Israel, November 5-7, 2013, Proceedings)

A High-Level Semantics for Program Execution under Total Store Order Memory - Dongol, Brijesh; Travkin, Oleg; Derrick, John; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2013 - 10th International Colloquium, Shanghai, China, September 4-6, 2013. Proceedings)

Temporal Reconfiguration Plans for Self-Adaptive Systems - Ziegert, Steffen; Wehrheim, Heike (Software Engineering 2013: Fachtagung des GI-Fachbereichs Softwaretechnik, 26. Februar - 2. März 2013 in Aachen)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul
Reconfigurable circuit devices have opened up a fundamentally new way of creating adaptable systems. Combined with artificial evolution, reconfigurable circuits allow an elegant adaptation approach to compensating for changes in the distribution of input data, computational resource errors, and variations in resource requirements. Referred to as ``Evolvable Hardware'' (EHW), this paradigm has yielded astonishing results for traditional engineering challenges and has discovered intriguing design principles, which have not yet been seen in conventional engineering. In this thesis, we present new and fundamental work on Evolvable Hardware motivated by the insight that Evolvable Hardware needs to compensate for events with different change rates. To solve the challenge of different adaptation speeds, we propose a unified adaptation approach based on multi-objective evolution, evolving and propagating candidate solutions that are diverse in objectives that may experience radical changes. Focusing on algorithmic aspects, we enable Cartesian Genetic Programming (CGP) model, which we are using to encode Boolean circuits, for multi-objective optimization by introducing a meaningful recombination operator. We improve the scalability of CGP by objectives scaling, periodization of local- and global-search algorithms, and the automatic acquisition and reuse of subfunctions using age- and cone-based techniques. We validate our methods on the applications of adaptation of hardware classifiers to resource changes, recognition of muscular signals for prosthesis control and optimization of processor caches.

Das Verteilungsproblem für mechatronische Systeme - Hüwe, Marcus